Dynamics response models of a solid-liquid fluidized bed - Ochoa, Javier (2002)
The solid liquid fluidized bed dynamic response model was developed with the MATLAB® toolbox and SIMULINK. The process represents the early recovery of lactic acid by ion exchange. Undesirable solid and liquid distribution along the columns could be avoided with successive and small concentration and velocity steps. From the dynamic response to successive and small steps equal processing time and improved dynamic adsorption capacity, with respect to the same change in one step, were found.